2010
DOI: 10.1186/1471-2148-10-123
|View full text |Cite
|
Sign up to set email alerts
|

Gene duplication and the origins of morphological complexity in pancrustacean eyes, a genomic approach

Abstract: BackgroundDuplication and divergence of genes and genetic networks is hypothesized to be a major driver of the evolution of complexity and novel features. Here, we examine the history of genes and genetic networks in the context of eye evolution by using new approaches to understand patterns of gene duplication during the evolution of metazoan genomes. We hypothesize that 1) genes involved in eye development and phototransduction have duplicated and are retained at higher rates in animal clades that possess mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 101 publications
(87 reference statements)
0
45
0
Order By: Relevance
“…Our studies in Drosophila have now described a key regulatory link between rhabdomeric cell type patterning and differentiation mediated by Glass and Pph13. Both of these molecules are conserved in Pancrustaceans (Liu and Friedrich, 2004; Rivera et al, 2010) and homologs can be found in other protostomes including Apylsia californica ((Mahato et al, 2014) and NCBI Ref. Seq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies in Drosophila have now described a key regulatory link between rhabdomeric cell type patterning and differentiation mediated by Glass and Pph13. Both of these molecules are conserved in Pancrustaceans (Liu and Friedrich, 2004; Rivera et al, 2010) and homologs can be found in other protostomes including Apylsia californica ((Mahato et al, 2014) and NCBI Ref. Seq.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our studies can serve as the entry point to answer a further question: does this pathway have broader conservation for rhabdomeric differentiation? It is indeed the case that the presence of homologs of Glass and Pph13 were discovered not only in Pancrustaceans, but also in other protostomes such as Aplysia californica , which have a different structural organization of eye in contrast to the compound eye but contain rhabdomeric photoreceptors (Jacklet, 1969; Jacklet et al, 1972; Liu and Friedrich, 2004; Mahato et al, 2014; Rivera et al, 2010). Thus further research on these protostomes will reveal whether Glass-Pph13 interplay acts as an evolutionary ancient transcriptional motif between the morphogenesis of various eye structures and the ensuing differentiation of rhabdomeric photoreceptor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…While gene duplications have occurred multiple times in invertebrate opsins (Rivera et al, 2010;Serb et al, 2013) and vertebrate cone opsins (Hunt et al, 1998;Matsumoto et al, 2006), visual rhodopsin is generally considered to be a single copy gene, with only a few exceptions. Several eel species have two rhodopsins, one freshwater (rh1fwo) and one marine (rh1dso), and expression shifts from the former to the latter following migration during maturation (Beatty, 1975;Hope et al, 1998;Zhang et al, 2000;Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Using each of the proteins listed above (excluding poriferan and cnidarian sequences) as 'bait' for database searches, we expanded the representation of genes in the phylogenetic analysis employing a pipeline of shell and perl scripts (Rivera et al, 2010;Tong et al, 2009). Each bait sequence from a major photolyase/cryptochrome clade was used to perform similarity searches using BLASTP (Altschul et al, 1997) of two non-redundant protein databases, UniRef50 and UniRef90, curated by UniProt (http://www.uniprot.org/).…”
Section: Introductionmentioning
confidence: 99%